Bilateral upper extremity trunk model for cross-country sit-skiing double poling propulsion: model development and validation - Chen, X.; Huang, Y.; Jiang, L.; Sun, Q.; Tian, Y.; Zhou, Z.; Yin, J.; Gao, Y.; Liu, C.; Huo, B. (Medical and Biological Engineering and Computing, 2023)
The subacromial impingement syndrome is a high-incidence injury for cross-country sit-skiing skier, which is often accompanied by muscle imbalance. However, at present, no musculoskeletal model has been identified for this sport. Thus, this research aimed to establish a bilateral upper extremity trunk (BUET) musculoskeletal model suitable for cross-country sit-skiing based on OpenSim software and verify the function of the model. By splicing three existing OpenSim models, an upper limb model with 17 segments, 35 degrees of freedom, and 472 musculotendon actuators was established. The clavicle and scapula were modeled as individual bodies and then connected to the torso through a three-degrees-of-freedom rotational joint and to the clavicle through a weld joint, respectively. The five lumbar vertebrae were established separately and coupled into a three-degree-of-freedom joint. Kinematics, kinetic, and EMG signal data of five 15-s maximal effort interval tests were obtained by using seven cameras, ergometers, and surface EMG synchronous collection. Based on the resulting rotator cuff muscle geometry of the model, simulated muscle activation patterns were comparable to experimental data, and muscle-driven ability was proven. The model will be available online (https://simtk.org/projects/bit) for researchers to study the muscle activation of shoulder joint movement.